Bio-convective micropolar nanofluid flow over thin moving needle subject to Arrhenius activation energy, viscous dissipation and binary chemical reaction. (June 2021) - Khan, Arshad; Saeed, Anwar; Tassaddiq, Asifa; Gul, Taza; Mukhtar, Safyan; Kumam, Poom; Ali, Ishtiaq; Kumam, Wiyada
Abstract: The study of nanofluid dynamics considering the bioconvection effects has significant applications, because nanofluid has remarkable capabilities for thermal transportation in comparison with pure fluids in various industrial and engineering applications. Keeping in view, such incredible characteristics the main objective of this work is to examine the influence of bioconvective micropolar nanofluid flow over a thin moving needle comprising of gyrotactic microorganism. The flow is also exposed to Arrhenius activation energy, binary chemical reaction and viscous dissipation. The governing equations are transformed to a dimensionless form by making use of a set of suitable variables and solved afterwards by employing homotopy analysis method (HAM). As main outcomes it is established in this work that, flow profiles decline with growing values of buoyancy ratio parameter, material parameter, volume fraction and bioconvection Rayleigh number. Thermal profile grows up with higher values of volumetric fraction, Brownian motion, Eckert number and thermophoretic parameter. Concentration profiles decline with growing values of thermosphoretic parameter, Brownian motion, Lewis number, chemical reaction parameter and grow up for increasing values of activation energy parameter. Moreover, a fine agreement between current results and the results available in literature has also established in current work.